Assessment of Impact of Containment During the COVID-19 Epidemic and Coping Behaviours Using Newly Developed Assessment Tools - Wong, Li Ping; Alias, Haridah; Danaee, Mahmoud; Lee, Hai Yen; Tan, Kit Mun; Tok, Peter Seah Keng; Muslimin, Mustakiza; AbuBakar, Sazaly; Lin, Yulan; Hu, Zhijian (Frontiers in Public Health, 2021)
Background The confinement measures during COVID-19 had a massive effect on physical and psychological health in public. This study assessed the impact of containment and coping behaviour among the Malaysia public during the COVID-19 pandemic. Questions assessing the impact of containment and coping behaviours were developed and psychometrically tested. Methods: Exploratory factor analysis (EFA) was conducted with the items using principal component analysis extraction and Varimax rotation. Partial least squares structural equation modelling was used to determine the relationship between coping and impact. Results: The 13-item of impact and 10-item coping instruments were developed with three dimensions identified through EFA. Both scales demonstrated excellent composite reliability and good convergent validity. The survey findings revealed that the impact on individual psychological aspects was prominent, followed by well-being and lifestyle. Mindfulness and physical coping strategies were most commonly reported. Coping through seeking help from health professionals and hotlines had a positive direct effect on well-being and lifestyle (b=0.231, p<0.001), psychological (B=0.132, p<0.001), and employment-related (0.194, p<0.001) impacts. Coping through mindfulness practice had a negative effect on well-being and lifestyle-related impact (B= -0.180, p<0.001) and employment-related impact (B= -0.096, p=0.008). Conclusions: The scales for measuring impact and coping behaviours have the potential to be used as a measurement tool in future studies. Health authorities should support individual coping as an important resilience-related factor to mitigate the impacts of containment during the pandemic.